Rancang Bangun Dashboard Perbandingan Penjualan Kamar Hotel (Studi Kasus: Hotel 88 Embong Malang Surabaya) - Ariyanto, Agus; Jusak, Jusak; Setyawan, Henry Bambang (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Hotel 88 Embong Malang Surabaya is one part of the PT. K. Hospitality is located in Central Jakarta. Hotel 88 is incorporated in the "Night Audit Community". Hotel 88 requires a comparison of sales of hotel rooms as a reference for the evaluation and manufacturing of new strategies in the competitive sales of hotel rooms. Currently recording sales and sales comparison hotel rooms are still using Ms. Excel. The problem today is Admin IT Hotel 88 calculates the sales data of existing hotel rooms in Night Audit Community and send the data via E-Mail every day. At the Head Manager and the Head of seeing and reading data on Ms. Excel then compare hotel with 88 existing hotels in the Night Audit Community. To overcome these problems, the hotel is 88 require a dashboard of sales comparison Hotel rooms and dashboard market segmentation for 88 itself. This helps Head Manager and the Head of easier reading comparative information through the dashboard as well as information about market segmentation. Based on trial results and evaluations conducted by Admin IT Hotel 88, which has been built Dashboard can be run through the website, and to run the dashboard takes less than 30 seconds. Dashboard also makes it easier to read the data comparison hotel room sales using charts and helped the Hotel 88 is no longer sending sales data room via E-Mail to Users